2004
DOI: 10.1086/423143
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Torque Tenovirus Infection and Serum Levels of Eosinophil Cationic Protein in Children Hospitalized for Acute Respiratory Diseases

Abstract: Children with bronchopneumonia have considerably higher Torque tenovirus (TTV) loads than do children with milder acute respiratory diseases (ARDs). Moreover, in children with ARDs, high TTV loads correlate with low percentages of circulating CD3+ and CD4+ T cells and with elevated percentages of B cells, suggesting that TTV might be immunomodulatory. Here, we show that, in children with ARDs, the presence of TTV and TTV load correlate with concentrations of serum eosinophil cationic protein. The possible mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 17 publications
2
27
0
Order By: Relevance
“…Furthermore, TTV-DNA and mRNA were detected in PBMCs from TTV À donors infected with supernatants only from TTV-infected stimulated cells [53]. Maggi et al [54] reported that the TTV viral load was significantly higher in children with bronchopneumonia than in children with milder ARD. The TTV viral load was inversely correlated with the number of CD4 þ cells, while it was positively correlated with the number of B cells.…”
Section: Target Cells Of Ttvmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, TTV-DNA and mRNA were detected in PBMCs from TTV À donors infected with supernatants only from TTV-infected stimulated cells [53]. Maggi et al [54] reported that the TTV viral load was significantly higher in children with bronchopneumonia than in children with milder ARD. The TTV viral load was inversely correlated with the number of CD4 þ cells, while it was positively correlated with the number of B cells.…”
Section: Target Cells Of Ttvmentioning
confidence: 99%
“…In this context, higher titers of TTV in nasal secretions from ARD children may be directly correlated with the presence of replicating regenerating epithelial cells and/or accumulating inflammatory cells. However, this assumption may be too simple, since the TTV viral load seems to be suppressed in the presence of more T-cells [54]. Touinssi et al [55] suggested that high TTV loads are associated with the level of immunoincompetence, because patients with a high TTV load (> 5 Â 10 3 to 5 Â 10 4 copies/mL) were statistically more frequent in haemodialysis, diabetic and low-CD4 þ HIV patients.…”
Section: Target Cells Of Ttvmentioning
confidence: 99%
“…9,10 All known TTV genotypes were detected because the assay targets a highly conserved segment of the viral untranslated region. 11,12 Reducing the volume of distilled water in which the extracted DNA was diluted and by increasing the volume of input DNA in the PCR reaction allowed to stretch the sensitivity to a lower limit of detection of 2.0 log 10 DNA copies/ml of plasma.…”
Section: Ttv Detection and Quantificationmentioning
confidence: 99%
“…Researchers have studied anelloviruses in the context of many diseases. Associations between anellovirus and acute respiratory disease have been described, but it is difficult to determine causation vs. correlation due to the ubiquitous nature of anelloviruses [9], [10], [11]. To date anelloviruses are still considered “orphan” viruses waiting to be linked to human disease [12].…”
Section: Introductionmentioning
confidence: 99%